A Review of Research on Technology-Supported Language Learning and 21st Century Skills - Shadiev, Rustam; Wang, Xun (Frontiers in Psychology, 2022)
Modern society needs people to be equipped with 21st century skills (e.g. critical thinking, creativity, communication, digital literacy or collaboration skills). For this reason, teaching and learning nowadays not only should promote students’ knowledge acquisition in various learning contexts but also their 21st century skills development, and language learning context is no exception. In this study, we reviewed research on technology-supported language learning and 21st century skills development. The reason is because earlier studies reviewed only articles related to language learning supported by technology and mostly focused on languages, language skills and technologies used. That is to say, 21st century skills development was not considered in earlier review studies. In the present study, we selected and reviewed 34 articles published between 2011 and 2022 (February) and focused on the following dimensions: (1) research focus such as language skills and 21st century skills; (2) theoretical foundations; (3) technologies; (4) learning activities; (5) methodology; and (6) findings. Our results were reported and discussed in the paper. In addition, we made recommendations for stakeholders such as educators and researchers in the field based on our results.